Do European tourists intend to revisit the same countries? Effect of satisfaction in European Union destinations - Štumpf, Petr; Vojtko, Viktor; Janeček, Petr (Routledge journals, Taylor and Francis LTD., 2020)
A high level of tourist satisfaction is one of the most common goals of sustainable tourist destinations. The general assumption is that a higher level of tourist satisfaction leads to higher tourist loyalty to destinations and, furthermore, increases revisits. This paper examines the relationships of how satisfaction, as well as the demographic, motivational, and behavioural characteristics of tourists, affect the intention to return for the main holiday to the same European Union (EU) country in the following year. We used the generalized linear model (GLM) with binomial logit link functions to reveal these relationships. The results show that satisfaction with the quality of accommodation plays an important role when EU citizens make decisions to revisit the same country. However, tourists’ motivation, age, travel distance, and country of origin influence the intention to revisit within the EU more significantly than the satisfaction attributes.
Keywords: Tourism Satisfaction, European Union, Destination loyalty, Revisit intention